Patient Data Security Evaluation In Hospital To Achieve SDGs 3.8.1 - Rasyad, Muhammad Fakhri; Lubis, Ratna Lindawati (eProceedings of Management, 2025)
This study examines Permata Hospital Cirebon's patient data security protocols to support SDG target 3.8.1 onexcellent health care. This qualitative study used purposive sampling, participant observation, and extensiveinterviews with four relevant participants. Five main topics emerged from the data analysis: data security incidentreporting, implementation challenges, socialization and training, incident evaluation, and data security systemimprovements. The biggest challenges are user adaption, vendor limitations, and technical dangers like malware andhacking. Despite data security socialization, formal training is lacking. Incidents are investigated reactively without asystematic auditing process. Regulations, data encryption, multi-factor authentication, and vendor risk managementare suggested. Organized training and SOP discipline are recommended by this study. In accordance with rules, theseprocedures should improve patient data security and enable digital health transition in Indonesia.Keywords- data security evaluation, SDGs 3.8.1, health digitalization, security management